PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN PERSEPSI HARAG TERHADAP KEPUTUSAN PEMBELIAN. (STUDI PADA KONSUMEN SMARTPHONE OPPO) - Fajar Luthfi Maulana, 12.05.51.0188; Soliha, Euis (Students Journal of Economic and Management, 2016)
The purpose of the study was to determine the effect of product quality, brand image and percepsion of price of on purchase decision (study on the consumers OPPO samrtphone). This study used purposive samplind using surveys and questionneires to 80 respondens. The data analysis technique use multiple linear regression. It was found that quality of the product positive and significant effect on purchase decisions OPPO samrtphone in Semarang. Furthermore, brand image and a significant positive effect on purchase decisions OPPO smartphone in Semarang. Whereas the perception of the price is not significant positive effect on purchase decisions OPPO smartphone in Semarang. Keyword: Product Quality, Brand Image, Price Perception, Purchase decision